CHOSEN FACTORS INFLUENCING COOPETITION IN WESTERN POLAND IN THE 2009-2011 PERIOD - Marek Tomaszewski (Acta Scientiarum Polonorum. Oeconomia, 2013)
Analysing the literature dealing with coopetition on both national and international levels, one cannot help but notice that this notion has recently become increasingly more popular. The same cannot be said however, of the notion of coopetition from a practical point of view. Apprehension related to coopetition have to do with the so-called limited confidence principle, applied by Polish entrepreneurs to other commercial entities. This principle has worked out well up until recently. However, the ongoing globalization and increasing pace of technological progress are forcing, especially small- and medium-sized enterprises, to pay closer attention to quite a different strategy of "sleeping with the enemy". The empirical part of the article indicates, how the chosen factors influence establishing coopetition. The list of factors include: PKD (Polska Klasyfi kacja Działalności - Polish Classification of Economic Activities) section, where the company customers come from, the distance from other delivery network participants, relations with those participants and technological class applicable to the company's technological process.